IMPROVEMENT OF THE LEGAL BASIS OF TRADEMARK PROTECTION AGAINST UNFAIR COMPETITION (World Bulletin of Management and Law, 2023)
this paper conveys the argument that trademark rights may be extended in scope so as to protect the competitive interests of the rightsholder independent from a finding of consumer confusion and at the same time promote the effectiveness of competition to the benefit of consumers. Various trader interests have been put forward as justifications of rational theories of trademark protection, most of them leaning towards the idea that the rights-holder has an interest in the economic exploitation of the advertising message incorporated into his trademark. The antecedent analysis examines the legitimacy of protecting trader interests in the internalization of advertising value through exclusive rights in trademarks
Keywords: trademark; competition